Pelaksanaanmalam Nisfu Sya’ban Oleh Masyarakat Di Desa Talang Pagar Agung.Kec. Pajar Bulan Kab.Lahat. - Hartati Hartati; Boris Brahmono; Yela Sinta Bella; Selpi Selpi; Annisa Fitriani; Dona Kontesa; Rizen Erlangga; Mayani Mayani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The night of nisfu sya'ban is an important event in the islamic calendar that is commemorated by the community as a time to ask for forgiveness and reflect on life. This study aims to understand the perceptions and practices of the people of Desa Talang Pagar Agung, Kec. Fajar Bulan, Kab. Lahat related to the night. The method used is a qualitative approach with in-depth interviews with community leaders and residents of DesaTalang Pagar Agung. The results of the study show that the community has various perceptions about the night of Nisfu Sya'ban, which range from spiritual beliefs to cultural traditions from generation to generation that have the benefits of getting forgiveness of sins, increasing worship, recording destiny, getting closer to Allah and can strengthen social relationships. The practices carried out include religious studies, tahlilan, joint prayers, and religious lectures that reflect their attachment to local religious and cultural values in everyday life. This study is expected to provide deeper insight into how Islamic traditions are integrated with local culture in Desa Talang Pagar Agung by practicing the night of Nisfu Sya'ban.